Programming with Visual Basic 4 - Hollander, Tom. (John Wiley and Sons, 1997)
Controls and properties. Event-driven programming. More code construcs. A few data structures. Trickier controls. Linking to databases. Treat it like an object. MDI applications. Olé for OLE. Extending visual basic.